Volume 2: Turbo Expo 2005 2005
DOI: 10.1115/gt2005-68513
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Emissions Performance of Existing Combustion Technologies for Syngas Combustion

Abstract: Syngas is composed of mixtures of H2 and CO and inerts such as N2, steam and CO2. The composition of syngas derived from oxygen and air-blown gasifiers is discussed. The low exhaust gaseous emissions potential of diffusion, lean premixed and rich catalytic combustors with representative oxygen and air-blown syngas fuels are evaluated. The evaluation is performed using network of well-stirred reactor models. The parameters of the reactor models are carefully chosen so as to represent the flow-physics in the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…ṁ and ṁ denote the total mass flow rate of the fuel and air entering the following reactors, respectively.For reference conditions, the residence times in PSR2 and PFR2 are 16 ms and 8 ms, respectively. The calculation was performed using the commercial software package CHEMKIN-PRO, and a detailed chemistry mechanism GRI-Mech 3.0 [21] was used to model the combustion and pollutant formation. However, in practice, it is unrealistic to mix the secondary mixture with all of the burnt gas from the upstream stage in a very short time.…”
Section: Crn Modelling Of the Staged Mild Combustormentioning
confidence: 99%
See 1 more Smart Citation
“…ṁ and ṁ denote the total mass flow rate of the fuel and air entering the following reactors, respectively.For reference conditions, the residence times in PSR2 and PFR2 are 16 ms and 8 ms, respectively. The calculation was performed using the commercial software package CHEMKIN-PRO, and a detailed chemistry mechanism GRI-Mech 3.0 [21] was used to model the combustion and pollutant formation. However, in practice, it is unrealistic to mix the secondary mixture with all of the burnt gas from the upstream stage in a very short time.…”
Section: Crn Modelling Of the Staged Mild Combustormentioning
confidence: 99%
“…Thus two sequential PSRs (PSR1 and PSR2) are used to model the first MILD combustion zone in the present study. PSR1 with a constant residence time of 1 ms [21] is used to mix and ignite the inlet fuel and air. PSR2 is used to simulate the MILD combustion zone in the first stage.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have previously been carried out at different pressure ranges in order to obtain an in‐depth understanding of the fundamental combustion characteristics of syngas flames focusing on measurements of burning rates, laminar flame speeds, ignition delay times and auto‐ignition properties, flame‐front structures and intrinsic instabilities; however, there has been a limited amount of research on NO x formation during syngas combustion at elevated pressure . While numerous researchers have experimentally studied combustion of syngas fuel mixtures under atmospheric pressure investigating the effect of temperature, equivalence ratio, H 2 /CO ratio and diluents on NO x formation, NO x emission data at relevant high pressure conditions are sparse. An experimental study conducted with low calorific value gas (LCVG) flames have revealed that increasing the pressure results in elevated NO emissions at constant methane concentration.…”
Section: Introductionmentioning
confidence: 99%